2013
DOI: 10.1111/jpn.12092
|View full text |Cite
|
Sign up to set email alerts
|

Induction of immune tolerance to caseins and whey proteins by oral intubation in mouse allergy model

Abstract: This study was designed to evaluate the effect of oral tolerance of caseins (CSN) and whey proteins (WP) in alleviating the allergic response to cow's milk proteins in Swiss albino mice raised on a milk protein-free diet. Oral tolerance was induced by feeding mice with 20 mg of CSN or WP once in a day for 4 days consecutively before immunization with respective protein by intraperitoneal (i.p.) injections (20 μg 200 per μl of PBS) using 2% of alum Al(OH)3 as adjuvant. Three weeks later, oral tolerance inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…The total IgE level in allergy mice was lower than those in previous studies (20,27). The above results were consistent with what we had predicted, since oral administration before sensitization suppressed the increase in total IgE (28,29). In this experiment, alum was used as the adjuvant for sensitization.…”
Section: Discussionsupporting
confidence: 81%
“…The total IgE level in allergy mice was lower than those in previous studies (20,27). The above results were consistent with what we had predicted, since oral administration before sensitization suppressed the increase in total IgE (28,29). In this experiment, alum was used as the adjuvant for sensitization.…”
Section: Discussionsupporting
confidence: 81%
“…To establish the role of IL-10 and TGF-β in tolerance compared with food allergy, various studies were performed. It was shown that cultured splenocytes of orally tolerized mice produce significantly higher concentrations of IL-10 than splenocytes of allergic mice ( 24 ). Furthermore, injecting IL-10 before applying a specific contact allergen inhibited the allergic response ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…gastrointestinal disorders [4,5]. Additionally, recent reports did not find detectable amounts of IL-4 using ex-vivo whole blood stimulation with commercial hydrolyzed protein diets in dogs with chronic enteropathy and healthy immunotolerant cats [26,27].…”
Section: Plos Onementioning
confidence: 98%
“…Whether through IgE induced mast cell degranulation or by humoral and cell-mediated reactions, the constant stimulus induces symptoms such as pruritus, vomiting, and diarrhea in dogs [2]. Several researchers reported increased TNF-α and IL-4, and decreased IL-10 in humans and mice with food allergies [3][4][5]. In dogs, previous studies highlighted the benefits of hydrolyzed proteins in preventing allergenic reactions.…”
Section: Introductionmentioning
confidence: 99%